At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
i will give prizes<3
Whats the first step?
Use the quadratic model y=ax^2+bx+c to solve problem use the second x,y pair and plug in (0,-4) -4=a(0)^2 + b(0) + c c=-4 do this for the next 2
wait so wouldnt the others be -20 and -20?
or was that just a weird circumstance?
(-2, -20) set up the equation again -20 = a(-2)^2 + b(-2) -4 notice we already know c=-4
Do you combine like terms
(4, -20) -20 = a(4)^2 + b(4) -4 notice we already know c=-4
Im having trouble solving the equation
ok we have to eliminate one of the variable to get a or b we do this by multiplying an equation by a number -20 = a(-2)^2 + b(-2) -4 lets simplify this add 4 to both sides and sqaure -2 -16 = 4a - 2b and -20 = a(4)^2 + b(4) -4 smae -16 = 16a + 4b here are those equations lined up what would you mult by to eliminate a variable??? -16 = 4a - 2b -16 = 16a + 4b
Im sorry man but im sure if i wasnt so stupid right now it would make sencexD sorry for wasteing your time man
well can you tell me what lost you i could explain a little more in detail
here are those equations lined up what would you mult by to eliminate a variable??? -16 = 4a - 2b -16 = 16a + 4b this part
sure let me go ahead you will see then i am sure -16 = 4a - 2b if we multiply this equation by 2 and then add to second eqaution we eliminate the b and then we can solve for a -16 = 16a + 4b -32 = 8a - 4b -16 = 16a + 4b ---------------- -48 =24a +0 now we divide both sides by 24 -2=a if i did that right a=-2 and c=-4
ssomthing like that
take the -2 and substitute back in an equation to get b -16 = 16(-2) + 4b -16 = -32 +4b add 32 both sides 16 = 4b divide both sides by 4 b=4 c=-4 and a =-2 our model is 0=-2a^2+4b - 4 if we did it right.
do have a question on what we did?
No man after what i read and pluged it in the equation it turned on a light buld Thanks!